Characteristics of Brain Tumor Patients at Dr. J. Leimena General Hospital From 2021-2024 - Windi Zamriani; Ivanmorl Ruspanah; Eka Astuty (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Brain tumors are intracranial neoplasms that affect neurological function and patients' quality of life. Although their incidence is lower than that of lung and breast cancer, brain tumors are progressive and have a high mortality rate. Both benign and malignant tumors can cause serious complications due to limited space within the skull and their proximity to vital functional centers. To date, there has been no research on the characteristics of brain tumor patients in Ambon City. Objectives: This study aims to describe the characteristics of brain tumor patients at Dr. J. Leimena General Hospital from 2021 to 2024 based on age, sex, clinical symptoms, type, and location of the tumor. Method: Quantitative descriptive with a cross-sectional approach, using medical records with total sampling technique. Results: The most common age group was 56-65 years (36.1%), female (63.9%), and the most frequent clinical symptom was headache (32.8%). The most common tumor type was extra-axial (50.8%), and the most frequent tumor location was in the frontal lobe (39.3%). Conclusion: Brain tumor patients are predominantly aged 56-65 years, mostly female, with headache as the most common symptom. The most frequent tumor type was extra-axial, most commonly located in the frontal lobe.